2018
DOI: 10.1002/lary.27556
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endoscopic and microscopic ear surgery in pediatric patients: A meta‐analysis

Abstract: Objectives Recently, the endoscope has been increasingly introduced for middle‐ear surgery. To evaluate the postoperative outcomes of endoscopic ear surgery (EES) in pediatric patients, we did a qualitative analysis with a systematic review and quantitative analysis with meta‐analysis of available literature. Methods Studies reporting the comparative surgical outcomes of EES in pediatric patients were systematically reviewed by searching the MEDLINE, PubMed, and Embase databases from database inception through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 51 publications
0
27
0
2
Order By: Relevance
“…TEES diminishes the need for a canal wall up mastoidectomy in some cases 12 and facilitates en bloc removal of cholesteatoma, with an improved chance of ossicular preservation 13 and decreased rates of residual and recurrent disease. 14 In studies comparing TEES to microscopic surgery for cholesteatoma, results have shown comparable or improved rates of control, 15 improved quality of life, decreased surgical morbidity, shorter healing time, and less postoperative pain due to avoidance of postauricular incisions. 16 TEES for tympanoplasty results in similar outcomes compared to microscopic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…TEES diminishes the need for a canal wall up mastoidectomy in some cases 12 and facilitates en bloc removal of cholesteatoma, with an improved chance of ossicular preservation 13 and decreased rates of residual and recurrent disease. 14 In studies comparing TEES to microscopic surgery for cholesteatoma, results have shown comparable or improved rates of control, 15 improved quality of life, decreased surgical morbidity, shorter healing time, and less postoperative pain due to avoidance of postauricular incisions. 16 TEES for tympanoplasty results in similar outcomes compared to microscopic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Many papers have described so far the outcomes and the benefits of endoscopic ear surgery, particularly with respect to tympanoplasty [1 , 6 , 12 , 13] , as well as many have performed a comparison between endoscopy and microscopy [14][15][16] . However, few studies explored the learning curve in endoscopic ear surgery [8][9][10] and none has focused on what is like for a surgeon already trained in microscopy to deal with the endoscopic learning curve and what are the main difficulties compared to a neophyte surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The authors who compared EES to microscopic ear surgery (MES) in myringotomy or myringoplasty as well as placing tympanostomy tubes reported results which are comparable if not better than MES. 5,6 Endoscopic technique was also reported very effective in other procedures, such as ossiculoplasty, stapedotomy, or cholesteatoma surgery, allowing visualization of the middle ear structures from angles which couldn't be possible with MES, therefore lowering the recurrence rate. Endoscopic ear surgery can be a valuable tool in education, allowing demonstration of surgical steps and anatomical relationships of tympanic membrane and middle ear.…”
Section: Endoscopic Removal Of Medially Migrated Tympanostomy Tubementioning
confidence: 99%